Transnational organized crime - Madsen, Frank G. (Routledge global institutions, 2009)
With organized crime estimated to generate billions of dollars every year through illegal activities such as money laundering, smuggling of people and goods, extortion, robbery, fraud and insider trading, authorities are increasingly working together to combat this increasing threat to international security and stability. In this book former police officer Frank Madsen provides a much needed, short and accessible introduction to transnational organized crime, explaining its history and the key current issues and clearly examining the economics and practices of crime in the era of globalization.